Primary care computing in England and Scotland: a comparison with Denmark - Denis Protti; Graham Wright; Shaun Treweek; Ib Johansen (Journal of Innovation in Health Informatics, 2006)
This paper compares the status of primary care computing in England and Scotland with that of Denmark. The rate of utilisation by Danish GPs is among the highest in the world and the MedCom national health network handles over 90% of the country's primary sector clinical communications. A high proportion of English and Scottish GPs also use computers in their clinical practices, and like their Danish colleagues, they benefit from more accurate and streamlined medications management, particularly in terms of repeat prescriptions. The historical forces and factors which influenced the development of primary care computing are identified and discussed.